21st-Century Media, 21st-Century Fiction (KULT_online, 2020)
The application of new media to 21st-century novels is the trigger of emerging narrative genres, which revolutionize the narrative panorama and leave space for innovative conceptual approaches. The influence of popular new media creates original circumstances for the development of new kinds of interaction between the storytelling and the reader/spectator, accentuating the rising need for social, multimedia engagements. The newest concepts and approaches of the emerging, wide fields of transmediality and intermediality in transmedial narratives are objects of the handbook ‘Fictions of the Internet’. From Intermediality to Transmedia Storytelling in 21st-Century Novels (2018) by Anna Weigel-Heller.